An interpersonal meaning analysis of the EFL student's talk in learning Descriptive Text at Junior High School - Maharani, Geana Sekar; Samsi, Yogi Setia (Prominent, 2024)
Abstract: Language is a type of action that is utilized to serve human needs by communicating information. It is concerned with interpersonal meaning or language-based human expressions. SFL analysis is significant to master in the grammatical field because it provides an overview for analyzing and interpreting the meaning of a written or spoken text. This study analyzed a conversation by student and teacher in learning writing descriptive text using interpersonal meaning. The aim of this study is to identify the mood system contained in transcript conversation students and teacher in junior high school. This study employed qualitative research due to the written form of analysis, and focused on analyzing speech function and the mood system that includes declarative mood, interrogative mood, exclamative mood and imperative mood. The findings of this study showed of the mood system contained in declarative mood, interrogative mood, exclamative mood and imperative mood. This showed that conversation student and teacher being analyzed contains information according to the function of the declarative mood, interrogative mood, exclamative mood and imperative mood, which is to describe information through a statement. Researcher found modality is probability, obligation, inclination, usuality in the data. Researcher for conversation, students, and teachers can better comprehend the underlying meanings and intentions conveyed through communication with the support of an in-depth knowledge of interpersonal meaning, which builds the interpretation and analysis of a variety of communication objects